Design Improvement Of Permanent Magnet Linear Synchronous Motor For Optimum Thrust Performance - Mohd Nasir, Nur Ashikin (2019)
Permanent Magnet Linear Synchronous Motor (PMLSM) introduces excellent performances in terms static characteristics and thrust density compare to other types of linear motor. Previously, a Permanent Magnet Cylindrical Synchronous Linear Motor (PMCLSM) was designed and developed. However, measurement result shows that the thrust, F of the PMCLSM was saturated at the current, I lower than its estimated rated current. One of the factors that caused the saturation is the unbalanced dimensions between the stator yoke and the coil of the PMLCSM. Therefore, the PMLSM was designed in this research to overcome this problem. The design of the PMLSM was accomplished by modified the structure parameters of the PMLSM. It was completed in two stages. Each model of the PMLSM was simulated by using FEM software where the simulation outputs were analyzed and compared to identify the best model. In the first stage of the PMLSM design, the yoke thickness, ty of the PMLSM was designed. From the simulation analysis, the PMLSM model with lower-side yoke thickness, ty2 is 3.0 mm was identified as the best model in the first stage of the PMLSM design. The model has an average thrust, Fave of 167 N at the current, I of 3.0 A. The model was chosen based on its insignificant thrust reduction. For the second stage of the PMLSM design, the structure parameters of the selected model in the first stage of the PMLSM design was chosen as the reference. In the second stage of the PMLSM design, the design was focused on the slot opening parameters with two different permanent magnet magnetization direction arrangement. The parameters of the slot opening are slot opening length, lt and slot opening height, ht. Meanwhile, the permanent magnet arrangements varied are N-S axial arrangement and Halbach arrangement. Based on the simulation results analysis, the PMLSM with Halbach arrangement with a combination of slot opening length, lt is 1.5 mm and slot opening height, ht is 1.0 mm was identified as the best model in the second stage of the PMLSM design. The model hence selected for the fabrication. Since the PMLSM’s driver design and development were not included in this research, the performance of the PMLSM was focused on the static characteristics. Therefore, the static thrust characteristics at each phase of the PMLSM was measured. The measurement results were then compared to the simulation outputs for result validation. However, due to the permanent magnet of the Halbach arrangement could not attached to the shaft permanently, the permanent magnet arrangement was changed to N-S axial arrangement. This is to ensure the sustainability of the PMLSM’s function. From the measurement, it shows that the thrust, F of the PMLSM with axial arrangement was able to be captured at excitation current, I higher than 1.5 A. At the excitation current, I of 2.0 A, the static thrust produced by the PMLSM with axial arrangement for phase A is 154.82 N. As a conclusion, the PMLSM with axial arrangement was capable in overcoming the thrust saturation faced by PMCLSM.